2021
DOI: 10.1007/s10620-021-07085-0
|View full text |Cite
|
Sign up to set email alerts
|

Video Capsule Endoscopy and Device-Assisted Enteroscopy

Abstract: Mark Hanscom Courtney Stead Harris Feldman Neil B. Marya David Cave

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 116 publications
(120 reference statements)
0
0
0
Order By: Relevance
“…The success rates of device-assisted enteroscopy techniques, such as double-balloon enteroscopy (DBE) and single-balloon enteroscopy (SBE), present variations compared to conventional methods such as video capsule endoscopy (VCE). The technical success rate for colonoscopy completion within this realm ranges from 85% to 98%, with additional findings reported in 14%-45% of cases [32]. Studies on DBE have consistently reported diagnostic rates within the range of 43%-81%, alongside treatment success rates ranging from 43%-84% [33,34].…”
Section: Success Rates Compared To Conventional Methodsmentioning
confidence: 89%
“…The success rates of device-assisted enteroscopy techniques, such as double-balloon enteroscopy (DBE) and single-balloon enteroscopy (SBE), present variations compared to conventional methods such as video capsule endoscopy (VCE). The technical success rate for colonoscopy completion within this realm ranges from 85% to 98%, with additional findings reported in 14%-45% of cases [32]. Studies on DBE have consistently reported diagnostic rates within the range of 43%-81%, alongside treatment success rates ranging from 43%-84% [33,34].…”
Section: Success Rates Compared To Conventional Methodsmentioning
confidence: 89%